PROSES BERPIKIR SISWA SMP DALAM MENYELESAIKAN MASALAH BENTUK ALJABAR DITINJAU DARI GAYA KOGNITIF - Hasya, Hurin Amalia; Zubaidah, Zubaidah; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractStudents' thinking process stages in solving problems covers the thinking process of understanding problems, arranging plans, executing plans, and looking back. The difference of students also can be analysed by their cognitive styles: Field Independent and Field Dependent. This research aims to describe junior high school students' thinking process on solving problems in algebra expression materials. After recognizing students' cognitive styles, teachers have larger vision to execute appropriate teaching method in class and give certain behaviors to students depending on their thinking process. This research is descriptive-qualitative research. The research subjects are eight students of class VIIID in SMPN 8 Pontianak. Four of them were students with Field Independent cognitive style, and the others were Field Dependent. The data collection methods used were Group Embedded Figures Test (GEFT), writing test and interview. Based on the results of writing test and interview, it showed that are 1) Students with cognitive style of Field Independent were able to understand problems, arrange plans and execute plans; 2) Students with cognitive style of Field Dependent were only able to understand problems without further performance. Keywords: Cognitive Style, Field Dependent, Field Independent, Thinking Process